Influence of white light illumination on the performance of a-IGZO thin film transistor under positive gate-bias stress - 汤兰凤 于广 陆海 武辰飞 钱慧敏 周东 张荣 郑有炓 黄晓明 (Chinese physics B, 2015)
The influence of white light illumination on the stability of an amorphous In GaZnO thin film transistor is investigated in this work. Under prolonged positive gate bias stress, the device illuminated by white light exhibits smaller positive threshold voltage shift than the device stressed under dark. There are simultaneous degradations of field-effect mobility for both stressed devices, which follows a similar trend to that of the threshold voltage shift. The reduced threshold voltage shift under illumination is explained by a competition between bias-induced interface carrier trapping effect and photon-induced carrier detrapping effect. It is further found that white light illumination could even excite and release trapped carriers originally exiting at the device interface before positive gate bias stress, so that the threshold voltage could recover to an even lower value than that in an equilibrium state. The effect of photo-excitation of oxygen vacancies within the a-IGZO film is also discussed.